GENETIC CHARACTERIZATION OF SOUTH AMERICA DOMESTIC GUINEA PIG USING MOLECULAR MARKERS - Diana Fernanda Aviles-Esquivel; Amparo Maria Martínez; Vincenzo Landi; Luz Angela Álvarez; Angelica Stemmer; Nílton Gómez-Urviola; Juan Vicente Delgado (Tropical and Subtropical Agroecosystems, 2018)
Twenty specific primers were used to define the genetic diversity and structure of the domestic guinea pig (Cavia porcellus). The samples were collected from the Andean countries (Colombia, Ecuador, Peru and Bolivia). In addition, samples from Spain were used as an out-group for topological trees. The microsatellite markers were used and showed a high polymorphic content (PIC) 0.750, and heterozygosity values indicated microsatellites are highly informative. The genetic variability in populations of guinea pigs from Andean countries was (He: 0.791; Ho: 0.710), the average number of alleles was high (8.67). A deficit of heterozygotes (FIS: 0.153; p<0.05) was detected. Through the analysis of molecular variance (AMOVA) no significant differences were found among the guinea pigs of the Andean countries (FST: 2.9%); however a genetic differentiation of 16.67% between South American populations and the population from Spain was detected. A poor genetic structure was found among the Andean countries with high genetic variability. The results suggest that it is necessary to take urgent measures to prevent further genetic erosion of native guinea pigs in the Andean countries with plans for recovery and conservation of this important genetic resource in South America.